EFFECT OF COMPRESSOR INLET TEMPERATURE ON THERMAL EFFICIENCY ROLLS ROYCE RB211 GAS GENERATOR IN COMBINED CYCLE POWER PLANT - Yulistio, Nanang; Wahyudi, Muhammad Prihadi Eko; Fitriyah, Qoriatul (Jurnal Rekayasa Mesin, 2024)
The combined cycle power plant must operate 24 hours without stopping so that in operation at any time an increase in the temperature of the gas generator RB211 can occur. The RB211 gas generator works well when the ambient temperature is low. The X combine cycle power plant uses a chiller to lower the inlet air temperature so that the air entering the compressor will be lower. The purpose of this study was to analyze and conclude the effect of the compressor inlet temperature on the thermal efficiency of the Rolls Royce RB211 gas generator in the combined cycle power plant. Data was collected by requesting historical data on September 5-11, 2022 in the central control room. The method used in this study is simple linear regression analysis because it only involves two variables. The independent variable is the inlet temperature of the compressor and the dependent variable is the thermal efficiency of the gas generator. It is known that the highest efficiency is at a temperature of 292,94 kelvin with a thermal efficiency value of 36,87% while the lowest efficiency is at a temperature of 301,89 kelvin with a thermal efficiency value of 35,61%. The regression analysis equation is Ŷ = 0,60665231-0,00082223X so the hypothesis results obtained through the significant F test with F table is that there is a significant effect between the compressor inlet temperature on the thermal efficiency of the gas generator.